PENGARUH KECERDASAN EMOSIONAL, LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI MODERASI - -, Indra Agung Yudistiro (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
The purpose of this research was to analyze the significance of the effect of emotional intelligence, work environment and the discipline of work and organizational commitment to the performance of teachers and analyze effect of emotional intelligence, work environment and the discipline of the employee performance with moderated by organizational commitment. The population are teachers SMKN Surakarta. Sample as much as 125 respondents with proportional simple random sampling techniques. Types of data used qualitative and quantitative. Data source used primary and secondary data. Data collection techniques used documentation, observation and questionnaires. Data analysis techniques used multiple regression and absolute difference value of the test. Result showed that emotional intelligence affected on teachers performance. Work environment affected on the teachers performance. Discipline affected on teachers performance. Organizational commitment affected on teachers performance. Organizational commitment does not moderate the effect of the emotional intelligence on teachers performance. Organizational commitment does not moderate the effect of work environment on teachers performance. Organizational commitment does not moderate the effect of discipline on teachers performance. Keywords: emotional intelligence, work environment, discipline, commitment organizational and teachers performance